2016
DOI: 10.1515/jpm-2015-0200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of measured postpartum blood loss after vaginal delivery using a collector bag in relation to postpartum hemorrhage management strategies: a prospective observational study

Abstract: This study suggests that PPH incidence may be higher than indicated by population-based data. Underbuttocks drapes are simple, objective bedside tools to diagnose PPH. Blood loss should be quantified systematically if PPH is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Similarly, Original Article SMJ many settings used collector bags as an effective tool for measuring postpartum blood loss after vaginal delivery in the third stage of labor. [3][4][5][6] However, the risk of PPH could be assessed in the antepartum or the first stage of labor as indicated in the study of Sittiparn and Siwadune that identified the risk factors associated with PPH and incorporated those risk factors into a risk score to predict PPH in normal labor. It could predict PPH in normal labor with sensitivity of 81.30% and specificity of 50.80% at the optimal cut-off score of four points or above.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Original Article SMJ many settings used collector bags as an effective tool for measuring postpartum blood loss after vaginal delivery in the third stage of labor. [3][4][5][6] However, the risk of PPH could be assessed in the antepartum or the first stage of labor as indicated in the study of Sittiparn and Siwadune that identified the risk factors associated with PPH and incorporated those risk factors into a risk score to predict PPH in normal labor. It could predict PPH in normal labor with sensitivity of 81.30% and specificity of 50.80% at the optimal cut-off score of four points or above.…”
Section: Introductionmentioning
confidence: 99%
“…They also recommended this method as a tool for the diagnosis of PPH. 12 In December 2016, the Royal College of Obstetricians and Gynaecologists (RCOG) released a new guideline relative to the prevention and management of PPH. They also confirmed the underestimation of postpartum hemorrhage by the visual estimation method and suggested the use of more reliable methods, including blood collecting drapes or the weighing of soaked swabs after vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…For these two large trials, the fit was also very good. We have also fitted a lognormal distribution to blood loss data using the reported percentiles from an observational study [ 11 ]. In all cases, we have found empirical evidence that the blood loss volume has a lognormal distribution, and can be described by a variant of this family of distributions, the threshold three-parameter lognormal distribution [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown empirically, elsewhere [ 4 ], that the distribution of postpartum blood loss volume is lognormal, using data provided by the authors from three trials that compared two drugs [ 1 , 9 ] or two management procedures for the third stage of labour [ 10 ], and one observational study [ 11 ]. We used this finding to propose an analysis approach based on the lognormal distribution, resulting in more efficient estimates of proportions and relative risk and in a reduction of the sample size needed in clinical trials that compare proportions between treatments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%